2021
DOI: 10.1371/journal.pone.0245715
|View full text |Cite
|
Sign up to set email alerts
|

PI3k inhibitors (BKM120 and BYL719) as radiosensitizers for head and neck squamous cell carcinoma during radiotherapy

Abstract: Approximately 500,000 new cases of head and neck squamous cell carcinoma (HNSCC) are reported annually. Radiation therapy is an important treatment for oral squamous cell carcinoma (OSCC). The survival rate of patients with HNSCC remained low (50%) in decades because of radiation therapy failure caused by the radioresistance of HNSCC cells. This study aimed to identify PI3K inhibitors that can enhance radiosensitivity. Results showed that pan-Phosphoinositide 3-kinases (PI3K) inhibitor BKM120 and class I α-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Studies have also shown that targeted inhibition of the PI3K-AKT-mTOR pathway can prevent cell repair of DNA damage, thereby making patients more sensitive to radiotherapy and chemotherapy [134]. This finding has been used to treat head and neck malignancies [135,136]. Besides, inhibition of PI3K-AKT-mTOR pathway in pancreatic cancer cells can inhibit cancer-associated fibroblasts (CAF), reduce interstitial fibrosis, and alter pancreatic cancer tumor microenvironment (TME), which will thereby increase the lethality of chemotherapy drugs [137].…”
Section: Kras Gene Mutation and Pancreatic Cancer Microenvironmentmentioning
confidence: 99%
“…Studies have also shown that targeted inhibition of the PI3K-AKT-mTOR pathway can prevent cell repair of DNA damage, thereby making patients more sensitive to radiotherapy and chemotherapy [134]. This finding has been used to treat head and neck malignancies [135,136]. Besides, inhibition of PI3K-AKT-mTOR pathway in pancreatic cancer cells can inhibit cancer-associated fibroblasts (CAF), reduce interstitial fibrosis, and alter pancreatic cancer tumor microenvironment (TME), which will thereby increase the lethality of chemotherapy drugs [137].…”
Section: Kras Gene Mutation and Pancreatic Cancer Microenvironmentmentioning
confidence: 99%
“…The presence of alterations in this pathway is related to a poor prognosis and resistance to radiotherapy and cytostatic drugs. Preclinical and phase II trials of PI3K/AKT/mTOR inhibitors (buparlisib and alpelisib) have demonstrated efficacy in monotherapy and in combination with chemotherapy [71,72] and radiotherapy [73][74][75]. In general, ongoing clinical trials are trying to elucidate the role of AKT and mTOR inhibitors in combination with chemotherapy and radiotherapy and in patients with resistance to them.…”
Section: Pi3kmentioning
confidence: 99%
“…Additionally, SGI-1776 and AZD-1208 (PIM kinase inhibitors) may overcome/delay resistance to alpelisib and produce additive/synergistic effects in tumor inhibition. [104][105][106][107][108][109][110][111][112][113] As it is pertinent to breast cancer, alpelisib was synergistic with the CKD4/6 inhibitor ribociclib in triple-negative cell lines and PDX models, 108 and showed synergy with the pan-HER TKI neratinib in inhibiting growth of HER2+ cell lines. 113 In summary, development of a biomarker for PI3Ki is an evolving field.…”
Section: Clinical Testing For Pik3ca Mutations: the Companion Diagnos...mentioning
confidence: 99%